Echocardiographic Evaluation of Aortic Stenosis – Normal Flow and Low Flow Scenarios - Burwash, Ian G (Eur Cardiol, 2014)
The echocardiographic evaluation of the patient with aortic stenosis (AS) has evolved in recent years, beyond confirming the diagnosis and measuring the resting mean pressure gradient or valve area. New echocardiographic approaches have developed to address the clinical dilemmas related to discordant haemodynamic data, asymptomatic haemodynamically severe AS and low-flow, low-gradient AS in order to better evaluate the disease severity, enhance the risk stratification of patients and provide important prognostic information. This article reviews the echocardiographic evaluation of the AS patient and focuses on the echocardiographic assessment of the haemodynamic severity, the prediction of clinical outcome and the use of echocardiography to guide patient management in the presence of normal flow and low flow scenarios.